Threshold response of stomatal closing ability to leaf abscisic acid concentration during growth - Giday, Habtamu (Oxford University Press, 2014)
Leaf abscisic acid concentration ([ABA]) during growth influences morpho-physiological traits associated with the plant’s ability to cope with stress. A dose–response curve between [ABA] during growth and the leaf’s ability to regulate water loss during desiccation or rehydrate upon re-watering was obtained. Rosa hybrida plants were grown at two relative air humidities (RHs, 60% or 90%) under different soil water potentials (–0.01, –0.06, or –0.08MPa) or upon grafting onto the rootstock of a cultivar sustaining [ABA] at elevated RH. Measurements included [ABA], stomatal anatomical features, stomatal responsiveness to desiccation, and the ability of leaves, desiccated to varying degrees, to recover their weight (rehydrate) following re-watering. Transpiration efficiency (plant mass per transpired water) was also determined. Soil water deficit resulted in a lower transpiration rate and higher transpiration efficiency at both RHs. The lowest [ABA] was observed in well-watered plants grown at high RH. [ABA] was increased by soil water deficit or grafting, at both RHs. The growth environment-induced changes in stomatal size were mediated by [ABA]. When [ABA] was increased from the level of (well-watered) high RH-grown plants to the value of (well-watered) plants grown at moderate RH, stomatal responsiveness was proportionally improved. A further increase in [ABA] did not affect stomatal responsiveness to desiccation. [ABA] was positively related to the ability of dehydrated leaves to rehydrate. The data indicate a growth [ABA]-related threshold for stomatal sensitivity to desiccation, which was not apparent either for stomatal size or for recovery (rehydration) upon re-watering.